Trends of Utilization of Antiseizure Medications Among Pregnant Women in Manitoba, Canada: A 20-Year Population-Based Study - Shouman, Walid; Delaney, Joseph A.; Kowalec, Kaarina; Ng, Marcus; Ruth, Chelsea; Falk, Jamieson; Leong, Christine; Alessi-Severini, Silvia; Lavu, Alekhya; Peymani, Payam; Eltonsy, Sherif (Frontiers in Pharmacology, 2022)
Background: Evidence from developed countries demonstrates that the use of anti-epileptic drugs (AEDs) has been increasing in the last decade. Pregnant women have a very challenging risk benefit trade-off in terms of AED utilization, and it is crucial to know if increased utilization is seen among pregnant women. Objective: To examine time-trends of utilization of AED therapies among pregnant women in Manitoba, Canada. Methods: We conducted a population-based cohort study using de-identified, linked administrative databases from Manitoba. Pregnancies between 1995 and 2018 were included. Four groups of pregnant people were created based on AED exposure and epilepsy diagnosis. Results: Of 273,492 pregnancies, 812 (3/1000) had an epilepsy diagnosis and were exposed to AEDs, 963 (3.5/1000) had an epilepsy diagnosis and were unexposed, and 2742 (10/1000) were exposed to AEDs and did not have epilepsy diagnosis. Overall, the number of pregnancies exposed to AEDs increased significantly from 0.56% in 1997 to 2.21% in 2018 (p<0.0001). Subgroup analysis by epilepsy diagnosis showed no significant change in AEDs exposure among women with epilepsy (0.37% [1997] to 0.36% [2018], p=0.24). A drop in carbamazepine use was observed, while the number of lamotrigine prescriptions increased from 6.45% in 1997 to 52% by 2018. AEDs use among pregnant women without epilepsy increased significantly from 0.19% in 1997 to 1.85% in 2018 (p<0.0001). In the total cohort of pregnancies, 1439 (0.53%) were exposed during their entire pregnancy, and 1369 (0.5%) were exposed in the first trimester. Clonazepam was the most used AED during the study period (1953 users, 0.71%), followed by gabapentin (785 users, 0.29%) and carbamazepine (449 users, 0.16%). Conclusion: No major shifts in the quantity of AEDs use over the study period were observed among pregnant women with epilepsy. However, there was a significant increase in AEDs use among pregnant women without epilepsy. The study results warrant further investigation into the implications of AEDs use in pregnancy for other indications than epilepsy.